Timing of Ketogenic Dietary Therapy (KDT) Introduction and Its Impact on Cognitive Profiles in Children with Glut1-DS-A Preliminary Study - Martina Barthold; Anne Jurkutat; Regina Goetz; Lucia Schubring; Juliane Spiegler; Ann-Sophie Fries; Lucia Kiesel; Joerg Klepper (MDPI AG, 2023)
The aim of this research was to characterize cognitive abilities in patients with Glut1-Deficiency syndrome (Glut1DS) following ketogenic diet therapy (KDT). Methods: The cognitive profiles of eight children were assessed using the Wechsler Intelligence Scale (WISC-IV). The effect of ketogenic diet therapy (KDT) on individual subareas of intelligence was analyzed considering the potential influence of speech motor impairments. Results: Patients with Glut1DS showed a wide range of cognitive performance levels. Some participants showed statistically and clinically significant discrepancies between individual subdomains of intelligence. Both variables, KDT initiation as well as duration, had a positive effect on the overall IQ score. Significant correlations were partially found between the time of KDT initiation and the level of IQ scores, depending on the presence of expressive language test demands of the respective subtests of the WISC-IV. Accordingly, the participants benefited les in the linguistic cognitive domain. The discrepancies in cognitive performance profiles of patients with Glut1DS can be attributed to the possibility of a negative distortion of the results due to the influence of speech motor impairments. Conclusions: The individual access skills of test persons should be more strongly considered in test procedures for the assessment of intelligence to reduce the negative influence of motor deficits on test performance. Specific characterization and systematization of the speech disorder are indispensable for determining the severity of speech motor impairment in Glut1DS. Therefore, a stronger focus on dysarthria during diagnosis and therapy is necessary.